Market survey/impact assessment - public education programmes to promote the CARICOM Single Market and Economy (CSME) and Caribbean Court of Justice : final report (Caribbean Media Consultants Port of SpainTT, 2001)
Analyzes the conduct of the CARICOM Single Market and Economy public education programme, as well as that of the implementation of the proposed Caribbean Court of Justice.
Keywords: FREE TRADE AREAS